Laser Welding of Cast Titanium and Dental Alloys Using Argon Shielding - Ikuya Watanabe, DDS, PhD;1 and D. Scott Topham, DDS2 (Journal of Prosthodontics, 2006)
This study investigated the effect of argon gas shielding on the strengths of laser-welded cast Ti and Ti-6Al-7Nb and compared the results to those of two dental casting alloys